Response to Comment on: Attitudes and Barriers to Physical Activity and Exercise Self-Efficacy Among Chinese Pregnant Women: A Cross-Sectional Study [Response to Letter] - Shang X; Ye L; Li L (Journal of Multidisciplinary Healthcare, 2024)
Xingchen Shang,1,2 Linfei Ye,1 Lin Li3 1School of Nursing, Yangzhou University, Yangzhou, People’s Republic of China; 2School of Nursing, Li Ka Shing Faculty of Medicine, The University of Hong Kong, Hong Kong, People’s Republic of China; 3Department of Nursing, The Affiliated Hospital of Yangzhou University, Yangzhou, People’s Republic of ChinaCorrespondence: Xingchen Shang, Email 007210@yzu.edu.cn